Early Marriage in Blitar Regency - Achmad Gatot Sunariyanto; Joel Rey Ugsang Acob; Heru Santoso Wahito Nugroho; Suparji Suparji; Sanglar Polnok; Wiwin Martiningsih (Health Notions, 2018)
Early marriage can cause several negative impacts, including vulnerability to incidents of domestic violence, an increased risk of dying during pregnancy and childbirth, and cutting off opportunities to continue education. By looking at some of the negative impacts as described above, prevention of early marriage is a very important effort in order to improve the reproductive health of the nation's future generations. That is why efforts to reduce the rate of early marriage are one of the main programs in the Department of Population Control, Family Planning, Women's Empowerment, and Child Protection in Blitar Regency, Indonesia. In order to participate in increasing the achievement of the aforementioned program, it is necessary to conduct a study to describe the achievement of the program to reduce the early marriage rate in Blitar Regency, so that in turn a recommendation can be proposed for improving strategies so that a reduction in the rate of early marriage in Blitar Regency can be realized in next year. This study is a descriptive study that aims to describe the achievement of the “Population, Family Planning and Family Development” program of the Department of Population Control, Family Planning, Women's Empowerment, and Child Protection of Blitar Regency, in 2018, especially efforts to reduce the rate of early marriage. This study was conducted during November 2018 in the working area of the Department of Population Control, Family Planning, Women's Empowerment, and Child Protection in Blitar Regency. The variable in this study is the age of marriage. Data was collected through a documentation study of secondary data in the form of raw data that is already available at the Department of Population Control, Family Planning, Women's Empowerment, and Child Protection of Blitar Regency. Data were analyzed using descriptive statistical methods, which consisted of the proportion of incidence of early marriage according to month-based time, prediction of the proportion of incidence of early marriage in the future (month-based), and the proportion of early marriage incidence according to sub-district-based clusters. The results showed that: 1) the proportion of the incidence of early marriage from month to month was not much different, with irregular fluctuations, 2) based on the proportion of early marriages per month, a trend line was drawn in the form of a polynomial equation, namely: y = 0.0011x2 - 0.0123x + 0.1357, 3) the average incidence of early marriage was 11.01, the sub-districts that had a high proportion of early marriage were Udanawu, Srengat, Kademangan, Bakung, Kanigoro, Garum, Sutojayan, Wlingi and Selopuro Districts. Furthermore, it was concluded that early marriage in Blitar Regency has an increasing trend, with a striking difference between sub-districts with the highest and lowest incidence of early marriage. Keywords: early marriage; Blitar Regency; predictive proportions